EVIDENCE BASED LEARNING: AN ANALYSIS OF IMPACT OF TEACHER’S DESIGN MODEL ON CONCEPTUAL UNDERSTANDING - Thote, Prashant; S, Gowri (International Journal of Research -GRANTHAALAYAH, 2021)
Lewis dot structure is taught in Chemistry at senior secondary school level. The competence to draw the Lewis dot structure and its interpretation lays foundation for advance learning. In the present paper attempt is made to investigate the impact of teacher made model to enhance deep conceptual understanding of Lewis dot structure in Chemistry. The concept is taught by using expository and discussion method but these teaching methods do not improve the students’ ability to construct their knowledge - as a result learners do not have deep conceptual understanding. An optional way to increase learner’s understanding in cognitive aspect is by using teaching aids developed by the teacher. Feasibility percentage of these models is 95%. The present research uses one group (pre-formative and post formative assessment) experimental design. Totally 35 students of Grade 12 partake in the study. Purposive sampling technique is used to draw the sample. Data is collected by using formative assessment before and after the treatment. Test score and t-test are the statistical tools used for the analysis of data. The content test validity is 96% and the reliability co-efficient is 0.86 on Spearman- Brown. Result of the present study illustrates that the model developed for teaching-learning of Lewis dot structure is effective to enhance the deep conceptual learning and to acquire intended learning outcomes. It is illustrated by the paired analysis of sample t with t score (-38.52) is less than the critical - t value (-2.03). There is a major difference in the scores of learners before and after the treatment. The effectiveness of teacher made Lewis dot structure model is determined by formative assessment both before and after the treatment. The score of cognitive skills (0.658) is categorized under moderate gain.